The impact of insurance coverage on the prenatal genetic counseling process: An exploration of genetic counselors' experiences with TRICARE. (23rd April 2019) - Brown, Jordan; O'Neill, Suzanne; DiNonno, Wendy; Hess, Olivia
Abstract: The prenatal genetic counseling process may be influenced by the patient's insurance coverage for both prenatal testing and termination. Major commercial insurance providers have different policies. TRICARE is the United States Department of Defense health program for uniformed service members. TRICARE provides coverage to approximately 9.4 million beneficiaries, including health plans, special programs, prescriptions, and dental plans. TRICARE's covered medical expenses are outlined in their policies, including those pertaining to genetic testing and termination. This qualitative study aimed to explore the extent to which insurance coverage of prenatal genetic testing and termination of pregnancy affect the genetic counseling process by exploring genetic counselors' experience with TRICARE. The majority of counselors stated that they did not change their overall counseling process for TRICARE patients. However, several counselors expressed that they changed the way they discussed cost with TRICARE patients, specifically in regard to genetic testing. Additionally, counselors provided their perceptions of their patients' emotional experiences. With the recent consolidation of the three TRICARE regions into two TRICARE Regional Office (TRO) regions and the renewal of the Laboratory Developed Tests Demonstration Project, the findings of this study are valuable in the evaluation of TRICARE's coverage of prenatal genetic services. Abstract : What is already known about this topic? To the authors' knowledge, there is no published literature examining TRICARE coverage of prenatal genetic counseling services. What does this study add? This study adds the unique perspective of prenatal genetic counselors experience with TRICARE. This study sets the stage for follow‐up research into patients' perspectives of TRICARE coverage of prenatal genetic counseling services.